2022
DOI: 10.1111/1759-7714.14718
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of interstitial lung abnormalities and immune checkpoint inhibitor‐induced interstitial lung disease in patients with non‐small cell lung cancer

Abstract: BackgroundInterstitial lung abnormalities (ILAs) are known to be a risk of drug-induced pneumonitis. However, there are few reports on the relationship between ILAs and immune checkpoint inhibitor-related interstitial lung disease (ICI-ILD). We retrospectively investigated the clinical signi cance of ILAs in patients with nonsmall cell lung cancer (NSCLC) receiving ICI. MethodsWe de ned ILAs as nondependent abnormalities affecting more than 5% of any lung zone, including ground-glass or diffuse centrilobular n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In nine studies on cancer treatment-related complications 20 , 22 , 27 33 , the prevalence of ILA ranged from 4 to 38%, and the follow-up periods varied from 0 to 12 years. Four studies adhered to the Fleischner Society definition, whereas the others had minor differences in ILA criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In nine studies on cancer treatment-related complications 20 , 22 , 27 33 , the prevalence of ILA ranged from 4 to 38%, and the follow-up periods varied from 0 to 12 years. Four studies adhered to the Fleischner Society definition, whereas the others had minor differences in ILA criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies adhered to the Fleischner Society definition, whereas the others had minor differences in ILA criteria. Four studies examined RP 27 , 28 , 32 , 33 , and another four studied ICI-ILD 20 , 29 31 . Notably, a single study focused on PPC 22 , which precluded the possibility of a comprehensive meta-analysis on PPC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the non-small lung cell carcinoma (NSCLC) cohort revealed that individuals with interstitial lung changes had a higher risk of developing immune-related pneumonia following immunotherapy [ 37 ]. Additionally, in patients with NSCLC receiving immune checkpoint inhibitor monotherapy, the presence of non-fibrotic ILAs was noted as a significant risk factor for early onset immune checkpoint inhibitor-induced interstitial lung disease (ICI-ILD) [ 38 ]. In stage III of NSCLC patients who have received definitive concurrent chemoradiotherapy but still have unresectable disease, pretreatment fibrotic ILA has been shown to be strongly related with symptomatic radiation pneumonitis and poor survival [ 39 ].…”
Section: Discussionmentioning
confidence: 99%